Effects of gender on stroke rates, critical speed and velocity of a 30-min swim in young swimmers - Greco, C. C.; Pelarigo, J. G.; Figueira, T. R.; Denadai, B. S. (Journal of Sports Science & Medicine, 2007)
Our objective was to analyze the effect of gender on the relationship between stroke rates corresponding to critical speed (SRCS) and maximal speed of 30 min (SRS30) in young swimmers. Twenty two males (GM1) (Age = 15.4 ± 2.1 yr., Body mass = 63.7 ± 12.9 kg, Stature = 1.73 ± 0.09 m) and fourteen female (GF) swimmers (Age = 15.1 ± 1.6 yr., Body mass = 58.3 ± 8.8 kg, Stature = 1.65 ± 0.06 m) were studied. A subset of males (GM2) was matched to the GF by their velocity for a 30 min swim (S30). The critical speed (CS) was determined through the slope of the linear regression line between the distances (200 and 400 m) and participant's respective times. CS was significantly higher than S30 in males (GM1 - 1.25 and 1.16 and GM2 - 1.21 and 1.12 m·s-1) and females (GF - 1.15 and 1.11 m·s-1). There was no significant difference between SRCS and SRS30 in males (GM1 - 34.16 and 32.32 and GM2 - 34.67 and 32.46 cycle·s-1, respectively) and females (GF - 34.18 and 33.67 cycle·s-1, respectively). There was a significant correlation between CS and S30 (GM1 - r = 0.89, GF - r = 0.94 and GM2 - r = 0.90) and between SRCS and SRS30 (GM1 - r = 0.89, GF - r = 0.80 and GM2 - r = 0.88). Thus, the relationship between SRCS and SRS30 is not influenced by gender, in swimmers with similar and different aerobic capacity levels.